Digitalisation and Artificial Intelligence for sustainable food systems - Marvin, Hans J.P.; Bouzembrak, Yamine; van der Fels-Klerx, H.J.; Kempenaar, Corné; Veerkamp, Roel; Chauhan, Aneesh; Stroosnijder, Sanne; Top, Jan; Simsek-Senel, Görkem; Vrolijk, Hans; Knibbe, Willem Jan; Zhang, Lu; et al. (Trends in food science & technology, 2022)
The European Commission (EC) has launched the European Green Deal communication, setting out the path for a fundamental transformation of Europe. Key element in this policy is a fully sustainable food system outlined in the farm-to-fork strategy. Such strategy requires a systems approach in which all aspects related to the production and consumption of sufficient and healthy food are considered, including economic, environmental (climate, ecosystems) and social aspects. Here, we present the systems approach concept for food production, following the farm-to-fork principle as embraced by the EC, and elaborate on how digitalisation and Artificial Intelligence (AI) can solve the challenges that a sustainable food system imposes. We present a number of research and innovation challenges and illustrate these by some specific examples. It is concluded that AI and digitalisation show great potential to support the transition towards a sustainable food system. This development will impact the roles and interactions of the actors in the entire value chain from farmers to consumers. Policy recommendations are made for a successful future implementation of AI in sustainable food production. •System approach is needed to achieve sustainable food systems.•AI and digitalisation are key to the transition towards sustainable food systems.•Data availability and use is important for actors in all stages from farm to fork.•Policy recommendations for a successful AI implementation in food systems.